Phenotype of Hypertension-altered Waist and its Association with the Components of Metabolic Changes in Gerontics - Giorgiet Galiano Guerra; Yamila Lastre Diéguez; Grettel Galiano Guerra; Dailenys García Céspedes; Yordanis Alberto Fonseca Atencio; Ariel Sosa Remón (Revista Finlay, 2020)
Foundation: abdominal obesity lis a specific phenotype of obesity and is characterized by affecting the upper half of the body, which associated to a group of metabolic factors increase cardiovascular risks. Objective: to determine the prevalence of hypetension phenotype – altered waist and its association with various components of the metabolic syndrome of gerontics admitted at the geriatric service of the Clinical Surgical Teaching Provincial Hospital Celia Sánchez Manduley of Manzanillo, Granma in the period from November 2017 – November 2018. Method: a cross descriptive study was conducted which included 180 aging patients admitted at the geriatric service who had personal history of hypertension. Results: phenotype hypertension diagnosis was established – altered waist in 157 subjects out of 180 studied, while in the age group of 70 to 79 and male sex were the most affected. The components of the metabolic syndrome with higher association with senescents affected by the endocrinopathy were dyslipidemia followed by glycaemia disturbances. In the group from 60 to 70 abdominal obesity- hypertension phenotype in individuals with overweight or normalbody mass index; while among nonagerians and the centenarian the association was more for normal weight. Hypertension – altered waist prevailed among overweight and normal weight of both sexes. Conclusion: there is a high prevalence of altered waist – hypertension in the studied older adults.